Case Report: Identification of Polygenic Mutations by Exome Sequencing - Liu, Yanfeng; Zheng, Zhongshi; Zhu, Qingling (Frontiers in Pediatrics, 2021)
The discovery of rare genetic variation through different gene sequencing methods is a very challenging subject in the field of human genetics. A case of a 1-year-old boy with metabolic acidosis and hypokalaemia, a small penis, growth retardation and G-6PD deficiency was reported. Since the clinical symptoms are complex and seem uncorrelated, the authors hypothesized that the child had chromosome or gene problems, and exome sequencing was applied to samples from him and his parents. Three main locus mutations in 3 genes were found in the proband, including the SLC4A1, FGFR1 and G6PD genes. A missense mutation (c.1766G>T, p. R589 L) was found in exon 14 of the SLC4A1 gene, which was a de novo mutation. Another missense mutation (c.1028 A>G, p. H343R) was found in exon 9 of the FGFR1 gene, which was also a de novo mutation. These findings further demonstrate the utility of exome sequencing in the diagnosis of rare diseases.